2011
DOI: 10.3109/14764172.2011.594058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 532-nm KTP and 1064-nm Nd:YAG lasers for the treatment of cherry angiomas

Abstract: Both KTP and Nd:YAG lasers were found to be effective methods. The Nd:YAG laser offered fewer treatment sessions, but a higher risk of scar formation. The KTP laser seems more advantageous, but in dark-skinned patients the Nd:YAG laser may be preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Recommendation Cherry angiomas may be safely and efficiently removed with KTP (532 nm), millisecond Nd:YAG (1064 nm), LPDL (595 nm) lasers and IPLS (GRADE 1C) …”
Section: Treatment Of Different Vascular Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendation Cherry angiomas may be safely and efficiently removed with KTP (532 nm), millisecond Nd:YAG (1064 nm), LPDL (595 nm) lasers and IPLS (GRADE 1C) …”
Section: Treatment Of Different Vascular Lesionsmentioning
confidence: 99%
“…Though millisecond Nd:YAG laser may generally require only one treatment, patients prefer the KTP laser as a less painful and safer option with the exception of pigmented skin where Nd:YAG laser is a good alternative …”
Section: Treatment Of Different Vascular Lesionsmentioning
confidence: 99%
“…They found that both were effective, with the Nd:YAG laser requiring less sessions than the KTP laser, but with a higher rate of complications [36]. Bulky lesions are ideal for the Nd:YAG laser since by nature the depth of coagulation is much deeper than the shorter wavelength vascular lasers.…”
Section: Cherry Angiomasmentioning
confidence: 99%
“…Because the absorption coefficient of hemoglobin is low at 1,064‐nm and because water is a competing chromophore, high fluences must be used to obtain vascular destruction, which increases the potential for collateral damage to the skin . The traditional millisecond Nd:YAG laser has been shown to be associated with a significantly higher risk of scarring than the KTP laser for the treatment of vascular lesions such as cherry angiomas . A 1,064‐nm Nd:YAG laser with a microsecond pulse duration may be able to treat small vessels with less pain and with a better risk profile than the traditional millisecond‐pulse‐duration Nd:YAG.…”
mentioning
confidence: 99%
“…2 The traditional millisecond Nd:YAG laser has been shown to be associated with a significantly higher risk of scarring than the KTP laser for the treatment of vascular lesions such as cherry angiomas. 4 A 1,064-nm Nd:YAG laser with a microsecond pulse duration may be able to treat small vessels with less pain and with a better risk profile than the traditional millisecond-pulse-duration Nd:YAG. The purpose of this prospective, single-center, proof-ofconcept trial was to evaluate the safety and efficacy of a microsecond-pulse 1,064-nm Nd:YAG laser in the treatment of facial telangiectasias.…”
mentioning
confidence: 99%